Identification of important organisational factors influencing safety work behaviours in construction projects - Jitwasinkul, Bhanupong; Hadikusumo, Bonaventura H. W. (Journal of Civil Engineering and Management, 2011)
Although the importance of organisational factors in human error has been acknowledged, the influence of organisational factors in the area of work behaviour in construction industry has rarely been examined. The first step of investigation should begin with identifying the relevant contributing factors affecting at-risk work behaviours. Thus, the aim of this research is to identify important organisational factors that will reduce at-risk work behaviours. The implications of these findings are further used to quantify and investigate the role of organisational factors as an integral feature of safety intervention. Case studies are used to identify and categorize organisational factors. This identification process begins with literature reviews as commonly performed. The literature related with organisational factors was used as a primary source to investigate the influences of organisational factors on at-risk work behaviours. Hence, semi-structured interviews and reviews of the company's documents were conducted involving safety experts and workers to gain experiential and practical knowledge. The obtained results identified seven important factors of Thailand construction industry: communication, culture, management commitment, leadership, organisation learning, empowerment, and reward system. The implications of particular applications from these factors are considered as critical features for handling work behaviours. In addition, empirical findings provide particularly insight factors from expertise in a practical way. Validations with previous publications of some factors are also discussed. The identified contributing determinants from empirical findings can be expected to be influential at different levels within an organization. Consequently, the proposed hypothetical casual models enables determination of disparity in their influences of organisational factors when considering interventions to reduce at-risk work behaviour or to promote safe work behaviours.Saugią elgseną statybose veikiančių organizacinių veiksnių nustatymasSantrauka. Organizacinių veiksnių įtaka žmonių klaidoms buvo pripažįstama ilgą laiką, tačiau tų veiksnių poveikis saugiai elgsenai statybos pramonėje yra mažai ištirtas. Pirmasis tyrimo žingsnis turėtų būti veiksnių, darančių įtaką rizikingai elgsenai, nustatymas. Tyrimo tikslas – nustatyti organizacinius veiksnius, kurie leistų mažinti rizikingą elgseną darbo vietose. Tai leis tirti ir kiekybiškai vertinti organizacinių veiksnių vaidmenį užtikrinant saugą. Organizaciniai veiksniai nustatomi ir skirstomi kategorijomis nagrinėjant pavyzdžius. Apžvelgiama literatūra, kuri naudojama kaip pirminis informacijos apie organizacinius veiksnius šaltinis, atliekama pusiau struktūrinta saugos ekspertų ir darbuotojų apklausa, apžvelgiami įmonės dokumentai. Gauti rezultatai leido nustatyti septynis reikšmingus veiksnius, būdingus Tailando statybos pramonei: komunikacija, kultūra, vadybininkų įsipareigojimai, vadovavimas, organizaciniai mokymai, galių suteikimas, apdovanojimų sistema. Nagrinėjama šių veiksnių reikšmė užtikrinant saugią elgseną darbo vietoje. Teigiama, kad empirinės žinios, sukauptos straipsnyje aprašomame tyrime, leis nustatyti veiksnių įtaką skirtingais organizacijos lygmenimis. Straipsnyje siūlomi modeliai leis vertinti organizacinių veiksnių įtakos rizikingai elgsenai darbe nevienodumą ir skatinti saugią elgseną.Reikšminiai žodžiai: organizaciniai veiksniai, saugaus darbo elgsena, Tailando statybos.